Localization of diacylglycerol lipase alpha and monoacylglycerol lipase during postnatal development of the rat retina - Cécyre, Bruno; Monette, Marjorie; Beudjekian, Liza; Casanova, Christian; Bouchard, Jean-François (Frontiers in Neuroanatomy, 2014)
In recent decades, there has been increased interest in the physiological roles of the endocannabinoid (eCB) system and its receptors, the cannabinoid receptor types 1 (CB1R) and 2 (CB2R). Exposure to cannabinoids during development results in neurofunctional alterations, which implies that the eCB system is involved in the developmental processes of the brain. Because of their lipophilic nature, eCBs are synthesized on demand and are not stored in vesicles. Consequently, the enzymes responsible for their synthesis and degradation are key regulators of their physiological actions. Therefore, knowing the localization of these enzymes during development is crucial for a better understanding of the role played by eCBs during the formation of the central nervous system. In this study, we investigated the developmental protein localization of the synthesizing and catabolic enzymes of the principal eCB, 2-arachidonoylglycerol (2-AG) in the retinas of young and adult rats. The distribution of the enzymes responsible for the synthesis (DAGLα) and the degradation (MAGL) of 2-AG was determined for every retinal cell type from birth to adulthood. Our results indicate that DAGLα is present early in postnatal development. It is highly expressed in photoreceptor, horizontal, amacrine, and ganglion cells. MAGL appears later during the development of the retina and its presence is limited to amacrine and Müller cells. Overall, these results suggest that 2-AG is strongly present in early retinal development and might be involved in the regulation of the structural and functional maturation of the retina.